The potential of Valeriana as a traditional Chinese medicine: traditional clinical applications, bioactivities, and phytochemistry - Li, Jianchun; Li, Xiaoliang; Wang, Changfu; Zhang, Manli; Ye, Minhui; Wang, Qiuhong (Frontiers in Pharmacology, 2022)
Valeriana plants are members of the Caprifoliaceae family, including more than 200 species worldwide. We summarized previous reports on traditional clinical applications, bioactivities, phytochemistry of Valeriana by searching electronic databases of Science Direct, Web of Science, PubMed, among others as well as some books. Some Valeriana species have been used as traditional medicines, demonstrating calming fright and tranquilizing mind, promoting Qi and blood, activating blood circulation and regulating menstruation, dispelling wind and eliminating dampness, regulating Qi-flowing to relieve pain, and promoting digestion and checking diarrhea, and treating diseases of the nervous, cardiovascular and digestive systems, inflammation, gynaecology, and others. Pharmacology studies revealed the effects of Valeriana, including sedative, hypnotic, antispasmodic, analgesic, antidepressant, anxiolytic, anticonvulsant, antiepileptic, neuroprotective, antibacterial, antiviral, cytotoxic and antitumor effects as well as cardiovascular and cerebrovascular system improvements. More than 800 compounds have been isolated or identified from Valeriana, including iridoids, lignans, flavonoids, sesquiterpenoids, alkaloids, and essential oils. Constituents with neuroprotective, anti-inflammatory, cytotoxic, and sedative activities were also identified. However, at present, the developed drugs from Valeriana are far from sufficient. We further discussed the pharmacological effects, effective constituents and mechanisms directly related to the traditional clinical applications of Valeriana, revealing that only several species and their essential oils were well developed to treat insomnia. To effectively promote the utilization of resources, more Valeriana species as well as their different medicinal parts should be the focus of future related studies. Clinical studies should be performed based on the traditional efficacies of Valeriana to facilitate their use in treating diseases of nervous, cardiovascular and digestive systems, inflammation, and gynaecology. Future studies should also focus on developing effective fractions or active compounds of Valeriana into new drugs to treat diseases associated with neurodegeneration, cardiovascular and cerebrovascular, inflammation and tumours. Our review will promote the development and utilization of potential drugs in Valeriana and avoid wasting their medicinal resources.